48. Short-latency somatosensory evoked potentials to median and tibial stimulation recorded by intracerebral electrodes. Issue 1 (January 2015) - Pro, S.; Specchio, N.; Rebessi, E.; Marras, C.E.; Fusco, L.; Vigevano, F.; Valeriani, M.
<x xml:space="preserve">Abstract</x> Preoperative evaluation, by means of intracerebral electrodes, in patients presenting with symptomatic drug resistant epilepsy, provides an opportunity to explore the S1 area in depth. We studied 7 pediatric patients with drug resistant epilepsy. Intracerebral electrodes were implanted in frontal, temporal and parietal lobes at different sites, depending on seizure types. SEPs were recorded to median and tibial nerve stimulation from the intracerebral electrode contacts referred to the earlobe ipsilateral to the stimulation. The analysis was addressed to the electrode contacts where an inversion of SEP component polarity was observed. A part from the median nerve N20 origin from the anterior bank of the postcentral gyrus, in 3 patients having electrode contacts close to medial surface of the parietal lobe, an inversion of polarity of the tibial nerve P40 component was observed. This is the first study demonstrating the origin of the tibial nerve P40 component from the medial surface of the S1 area by using intracerebral SEP recording.